PREAMBLE DETECTION IN WIMAX 802.16E USING OFDM WITH AWGN CHANNEL (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
WiMAX works on high data rate and it is a wireless technique so fading and attenuation in the signals is presence due to noise, inter symbol interference, inter carrier interference etc. OFDM modulation technique is used to work on multicarrier. OFDM works on orthogonality so presence of ISI is neglected. In this paper we used different methods are MSC, MGM, MINN, MML. MINN method is batter than the other is shown by the results. In correlation methods varying the value of correlation lag and find out what is the effect on detection technique. In this preamble detection method we used different communication channel AWGN and also used modulation techniques QAM with OFDM. The performance has been concluded based Sample versus Detection value and output through MATLAB-R3013a Simulation